Prevention of Malaria in Pregnancy: What Do the Pregnant Women of Nigeria Know and Do about It? - Stephen Kalu; Laurent Cleenewerck; Kabiru AbuBakar Gulma; Devender Bhalla (Hindawi Limited, 2022)
Objective. We assessed knowledge, attitude, and practice regarding two malaria prevention measures (long-lasting impregnated mosquito nets, LLINs, and intermittent preventative therapy with sulphadoxine-pyrimethamine (IPTp-SP)) among pregnant women in Nigeria. Methods. Pregnant women selected from among the four communities of Nnewi were interviewed by using a semistructured, interviewer-administered questionnaire on the respondents' demography, knowledge of the cause, consequences, and malaria prevention methods. Also, a total of 48 focused group discussions, 24 key informant interviews, and 24 in-depth interviews were held among women leaders, village heads, pregnant women, community health workers, husbands of pregnant wives, and drug and insecticide-treated net sellers. Results. A total of 384 women (88.0% third trimester, 90.0% literate, and 41.1% primigravidae) participated. About 80.0% suffered from malaria during their current pregnancy. The majority was aware of the cause of malaria, local name of malaria, mode of transmission, risk of malaria among pregnant women, etc. However, their knowledge and attitude were inadequate regarding the symptomatology and complications of malaria in pregnancy, benefits of sleeping under the net or taking chemoprophylactic doses, or the concurrent use of both. About 80.0% had LLINs, yet only 41.5% slept under it the previous night. Only 31.0% had IPTp-SP doses under direct observation. Only 35.9% had a good understanding of IPTp-SP during pregnancy. Conclusion. Our work presents important practice gaps associated with the prevention of malaria during pregnancy. The pregnant women seemed to be aware of the basic concepts related to malaria but that does not translate into adequate attitude and practice necessary for malaria reduction.